Truth and Justice in the Transition to Democracy in the 1990s State Policies and the Human Rights Movement [Verdad y Justicia en la Transición a la Democracia en Los Años Noventa: Políticas del Estado y Movimiento de Derechos Humanos] - Garces-Duran, M (Universidad de Concepcion, 2022)
Truth and justice in the field of human rights constituted one of the greatest challenges in the transition to democracy. In this article the hypothesis is that in Chile, the first governments of the transition divided both tasks, prioritizing the truth and proposing justice to the extent possible , a situation that generated conflicts and distance with associations of victims of the repression and more broadly with the human rights movement. These distances, however, it is hypothesized, favored a persistent and radical option for historical memory on the part of the human rights movement. © 2022, Universidad de Concepcion. All rights reserved.